Influence of Web Pages on the Choice of Tourist Destination - Coronel-Chugden, José-Walter; Moreno-Quispe, Luz Arelis (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The study identifies the information media that influence young people to travel to a tourist destination. The research is basic, descriptive and mixed-method. The data was collected through a questionnaire completed by 240 young people. The results indicate that websites are influential information media for young people when it comes to traveling to a destination. The majority prefer a trip within their region and in summer, opting for beach tourism, with a budget of 100 to 300 soles. These findings are relevant for creating content and promoting visual culture in this segment of the population.